Circular Economy in Spanish SMEs: Challenges and opportunities. (1st June 2018) - Ormazabal, Marta; Prieto-Sandoval, Vanessa; Puga-Leal, Rogério; Jaca, Carmen
Abstract: The important role of Small and Medium Enterprises (SMEs) in most economies underpins this research, which develops an empirical analysis that allows us to explore the potential for implementation of the Circular Economy in SMEs and the barriers and opportunities they may distinguish from it. To that end, a survey was carried out in Navarra and the Basque Country, Spain. The main results show that companies are focused on complying with the law and, in many cases, they are worried about their company's image. Moreover, they do not tend to be committed to environmental issues because they do not think it would increase their profits and competitiveness. The focus on cost savings became clear from the Factor Analysis applied to the Take-Transform and Recovery phases of the Circular Economy. In this sense, three factors were associated with the companies' perception of the Circular Economy: 1) Material Provision, 2) Resources' Reutilization and 2) Financial Advantage. With regard to the barriers, another Factor Analysis suggested two different categories of barriers: Hard barriers and Human-based barriers, each requiring different strategies for addressing them, must be considered. Finally, the study briefly examines the integration opportunities between SMEs with other companies and industry associations or clusters to develop industrial symbiosis and close their materials loop.